Nanocrystalline intermetallics in Al-Cu-Fe-Cr decagonal quasicrystalline alloy - Yadav T.P.; Mukhopadhyay N.K.; Srivastava O.N. (My University, 2025)
In the present investigation, an Al-Cu-Fe-Cr decagonal quasicrystalline alloy synthesized by a slow-cooling technique was mechanically milled in a high-energy ball mill for various times ranging up to 100 hours under liquid hexane medium at the speed of 400rpm with a ball to powder ratio of 40:1. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), differential thermal analysis (DTA), and energy-dispersive X-ray analysis (EDX) were employed to characterize the as-cast, milled, and annealed samples. Powders milled for more than 10h contained predominantly the B2-type nano-crystalline phase with a lattice parameter of 0.29nm. The 100h milled powder was annealed in air at 500C for 20-40h. It was observed that 40h annealed sample shows the best yield for the fabrication of nanospinel. The processing technique could be optimized to manufacture the composites of nano-quasicrystal, nano-B2, and nanospinels. These materials may be further investigated as a suitable material for pigment industries. © 2012 Taylor and Francis Group, LLC.